The effect of leadership styles towards person organization fit among teachers in Sekolah Kebangsaan Batu Laut / Nur Shuhada Adzam Yukhairiz - Adzam Yukhairiz, Nur Shuhada (Faculty of Business and Management, 2017)
This research made to study on the effect of leadership style towards person organization fit among teachers in Sekolah Kebangsaan Batu Laut (SK Batu Laut) at Selangor. This study aims on three leadership styles that affects person organization fit which are transformational leadership, charismatic leadership and democratic leadership. A good person organization fit is important in order to retain employees in the organization. Transformational leadership, charismatic leadership and democratic leadership will be discussed to see if it will affect person organization fit. In this research, it includes thirty respondents from different age, working length and different education background. Data was collected through questionnaire that had been distributed to the respondents in SK Batu Laut. Result of the present research shows that there was significant relationship between all the leadership styles used in this research which are transformational leadership, charismatic leadership and democratic leadership. This study also used regression analysis to identify which of the leaderships that had most been influence the person organization fit. This study is beneficial to the organization as it could help person fit with the organization. Recommendations for the future also have been discussed.